Research on intercropping from 1995 to 2021: a worldwide bibliographic review - Tang, Yurui; Qiu, Yurong; Li, Yabing; Xu, Huasen; Li, Xiao-Fei (Plant and soil, 2025)
Background and aims Intercropping or crop mixture is an agroecological strategy to optimize resource-use efficiency and crop yield. In recent decades, therefore, intercropping has gained increasing attention as a more sustainable land management alternative to monoculture-oriented intensive agriculture. However, few studies have attempted to perform a comprehensive and systematic review on this subject from a bibliometric perspective. Methods This study carried out a quantitative bibliometric analysis to explore the characteristics of publications, research hotspots, and future frontiers regarding intercropping globally from 1995 to 2021. Data of the publications were obtained from the Web of Science Core Collection database. Results A total of 7574 publications in intercropping research were identified. The research field of intercropping entered a rapid development stage in 2007, with Chinese scholars and research institutes contributing the most. The two journals with the highest h-index and global total citations are Field Crops Research and Plant and Soil. Research themes on intercropping have evolved over time, with the focus shifting from yield and plant interspecific interactions to sustainable agriculture. Moreover, keyword analysis showed that research frontiers were mainly concentrated on sustainable intensification, microbial community, climate change adaptation, biodiversity, and soil fertility. Conclusions The intercropping field continues to develop, attracting the attention of scholars around the world, and the research topics are booming as the research output increases. Future research will pay more attention to long-term agricultural sustainability.